Model and application of cyberspace information system - Jilong WANG; Shuying ZHUANG; Congcong MIAO; Changqing AN (Tongxin xuebao)
For the visualization of cyberspace is still using the traditional geographic information system,which makes it difficult to truly express the characteristics and laws of cyberspace,a multi-scale,multi-dimensional and multi-view cyberspace information system model was proposed to take the cyberspace information system as a concept parallel to the geographic information system,that was,the geographic information system supported visualization based on the geographic coordinate system,and the cyberspace information system supported visualization based on the coordinate system of cyberspace itself.Then,the basic concepts of cyberspace information system were defined to provide a theoretical foundation for later research,and the key technologies,part of exploratory research work including the coordinate system,scale,multi-dimensional expression model and application cases were expounded.According to the prototype developed,the cyberspace information system is more convenient for the display and processing of cyberspace affairs.